2001
DOI: 10.1002/cfg.70
|View full text |Cite
|
Sign up to set email alerts
|

Featured Organism: Reductive evolution in bacteria: Buchnera sp., Rickettsia prowazekii and Mycobacterium leprae

Abstract: Obligate intracellular bacteria commonly have much reduced genome sizes compared to their nearest free-living relatives. One reason for this is reductive evolution: the loss of genes rendered non-essential due to the intracellular habitat. This can occur because of the presence of orthologous genes in the host, combined with the ability of the bacteria to import the protein or metabolite products of the host genes. In this article we take a look at three such bacteria whose genomes have been fully sequenced. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
(13 reference statements)
4
25
0
Order By: Relevance
“…Our comparison of “bad bugs” and their respective controls confirmed the findings of previous studies [3]-[9], revealing a significant reduction in the genome size of “bad bugs”. This genome reduction was accompanied by a significant decrease in ORF content, which demonstrates that many genes are progressively disappearing from the genomes of “bad bugs”.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our comparison of “bad bugs” and their respective controls confirmed the findings of previous studies [3]-[9], revealing a significant reduction in the genome size of “bad bugs”. This genome reduction was accompanied by a significant decrease in ORF content, which demonstrates that many genes are progressively disappearing from the genomes of “bad bugs”.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, comparative genomic studies have revealed that in some cases, the genomes of bacteria, such as Rickettsia or Mycobacteria spp. [3][5], are reduced [4], [6][10]. For example, the genomes of Mycobacterium leprae , Yersinia pestis and Salmonella Typhi contain hundreds of degraded genes.…”
Section: Introductionmentioning
confidence: 99%
“…Reductive evolution involves the loss of nonessential bacterial genes in the host environment, including analogous gene products manufactured by the host that can be exploited by the bacterium (37). Consistent with irreversible host adaption in P314, MSHR6686 has cumulatively lost 285 kb at four distinct loci.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that the virulence potential of pathogenic bacteria is inversely proportional to overall genome size and gene content (Georgiades and Raoult, 2011), an observation which has been broadly demonstrated for phylogenetically dissimilar intracellular (Moran, 2002; Wixon, 2001) and extracellular (Georgiades and Raoult, 2011) disease-causing agents. Genome size itself has been shown to be a better predictor of bacterial virulence than the absolute number of classical “virulence factor” genes in comparing pathogenic bacteria compared to non-virulent or less-virulent counterparts (Georgiades and Raoult, 2011; Merhej et al, 2013), likely reflecting the process of gene loss during host adaptation (Merhej et al, 2009).…”
Section: Discussionmentioning
confidence: 99%